From Kampus To Kampung : Sebuah Langkah Kecil Membangun Akuntabilitas Nagari - Amy Fontanella; Akhnof Tria Kurnilah; Freshy Indrianti; Haniva Dela Gusta; Rido Putra; Gusranti Yuvitasari (Universitas Negeri Padang, 2018)
This community service activity was conducted in Nagari Koto Laweh Kec. Lembang Jaya Kab. Solok Prov. West Sumatra. This activity aims to improve the competence of nagari devices in financial management and the use of Village Finance System (SisKeuDes) application. In addition, this activity also aims to raise awareness and understanding of nagari society on the importance of good financial management. This activity is motivated by problems experienced by partners related to the limited human resources in financial management and weak control of the surrounding community. This activity is carried out through two stages: first, financial management training and workshop on the use of SisKeuDes application for the nagari staff, both public education about household / business finance management. The results of this research are the improvement of nagari capability in implementing financial management, the availability of nagari finance management module which is easy to be understood by the nagari staff, the existence of simple application support in order to facilitate the preparation of nagari government report, draft article, the increasing of understanding and awareness of the importance good financial management.